From victims to survivors: Does job passion mitigate the impact of social undermining on turnover intention? - Tosun Burcu; Kibaroğlu Gamze Güner; Basım Hamdullah Nejat; Çetin Fatih (Journal of Economics and Management, 2025)
Aim/purpose – Social undermining actions in workplaces may adversely affect employee performance and job satisfaction, eventually leading them to leave the organization. This study aims to examine whether the level of job passion exhibited by employees targeted by social undermining impacts their inclination to remain employed at the organization.